China Urban Services and Governance - Brixi, Hana (The World Bank, 2009)
The study addresses governance challenges in public service delivery in China. It builds on the citizen scorecard survey conducted in five Chinese cities in 2006 to gauge citizens' experience with public services, and demonstrates the usefulness of citizens' feedback for policy development and implementation. The survey found that citizens were generally pleased with urban public services, but worried about the associated fees. Compared with the official urban residents, the urban poor and rural migrants in cities reported sharper utilization constraints, lower readiness to complain or pay informal fees, and a much larger income share spent on public services. The reported citizens' perceptions sometimes diverged from the evidence and pointed to significant information asymmetries. Explaining the survey results, the study reveals problems of inadequacy, inequality and misaligned incentives in public resource allocation. The study presents several successful experiments reducing the dependence on user fees in basic education and primary healthcare. It recognizes that China has been undertaking comprehensive reforms to enhance equity and quality in public service delivery. Such reforms have included measures to strengthen the regulatory, monitoring, and enforcement systems and accountability relationships. In the context of the ongoing reforms, this study highlights the need to: a) hold the provincial governments accountable for public service delivery performance; b) develop effective mechanisms to align public resources and incentives at each level of government with the national priorities; and c) develop proper means to empower the citizens. In this context, the study affirms that the Chinese government is rightly placing reforms in the intergovernmental, administrative, and public finance systems at the top of its agenda